Additive manufactured self-powered mechanoelectric sensor as the artificial nucleus pulposus for monitoring tissue rehabilitation after discectomy. (1st June 2022) - Shi, Yunsong; Wang, Kun; Feng, Xiaobo; Li, Shuai; liang, Hang; Li, Gaocai; Li, Wenqiang; Ke, Wencan; Chen, Annan; Yang, Xiao; Yang, Lei; Yan, Chunze; et al.
Abstract: The capability to monitor the mechanical forces on the intervertebral disc (IVD) after discectomy could develop personalized rehabilitation strategies to benefit the patients´ healthy recovery. However, traditional nucleus pulposus (NP) substitutes are mainly hydrogels which can only physically fill the defect after discectomy without sense the mechanical stress. Here we demonstrate an additive manufactured NP substitute (AMNPS) that can sense the mechanical stress in the IVD with a self-powered capacity. When the AMNPS suffers the stress from the spine bending, the mechanical energy can be converted into electrical signal by the AMNPS and the whole mechanical sensing process is self-powered. To illustrate the capabilities of the AMNPS, we use it to monitor the spine bending of a goat in vivo, illustrating the potential application of the device to monitor the tissue rehabilitation after discectomy. Graphical Abstract: ga1 Highlights: A nucleus pulposus substitute that can self-powered sense bending of the spine is proposed. The nucleus pulposus substitute can monitor the stress in the intervertebral disc in vivo . The multi-layered 3D printing technique has been used to generate the nucleus pulposus substitute.